An Investigation to Integrate Optimum Long-Term Planning with Short Planning in Underground Mine Production Scheduling - Topal, Erkan; Nehring, M.; Kizil, M.; Knights, P. (Australasian Institute of Mining and Metallurgy, 2010)
Generating short- and long-term mine production schedules in isolation and independently from each other means that only a local optimum can be achieved when each scheduling phase is carried out. The globally optimal solution however, can be achieved when integrating scheduling phases and accounting for the interaction between short-term and long-term activities simultaneously. This paper addresses the task of integrating short- and long-term production plans by combining the short-term objective of minimising deviation to targeted mill feed grade with the long-term objective of maximising net present value (NPV) into a single mathematical model. A case study is presented which compares the present values of the same stope data set scheduled via separate long and short-term models and than by the proposed integrated model which applies a predetermined penalty for each tonne of metal deviation to target for the respective ore tonnage being processed. This allows an operation to obtain a globally optimal scheduling regime when taking into consideration the cost and loss of value resulting from fluctuations in grade to the mill over the short-term.